A study of differential circRNA and lncRNA expressions in COVID-19-infected peripheral blood - Yingping Wu (Nature Portfolio, 2021)
Abstract To conquer the worldwide outbreak of COVID-19 virus, a large number of studies have been carried out on COVID-19 infection, transmission and treatment. However, few studies have been conducted from the perspectives of circRNA and lncRNA, which are known to be involved in regulating many life activities, such as immune tolerance and immune escapes, and hence may provide invaluable information in the emerging COVID-19 infection and recurrence. Moreover, exosomes has been reported to play an important role in COVID-19 recurrence, and thus may interact with the expression of circRNA and lncRNA. In this work, we sequenced circRNA, lncRNA and mRNA from recurrent COVID-19 patients and healthy people, and compared the differences. GO and KEGG enrichment analysis show that differentially expressed circRNA and lncRNA are mainly involved in the regulation of host cell cycle, apoptosis, immune inflammation, signaling pathway and other processes. The comparison to exosomes related databases shows that there are 114 differentially expressed circRNA, and 10 differentially expressed lncRNA related to exosomes. These studies provide reference for exploring circRNA and lncRNA to study the infection mechanism of COVID-19, their diagnostic and therapeutic values, as well as the possibility to employ them as biomarkers.